Use of technology in biology education – case of infrared thermal imaging. Issue 3 (27th May 2022) - Wong, Choun Pei; Subramaniam, R.
ABSTRACT: While the use of ICT technologies in biology lessons is becoming more pronounced, it is not yet the case for those related to the use of advanced technologies. In this article, we focus on the use of an infrared camera for developing applications in biology. Infrared thermal imaging has become increasingly affordable, and it is now time for biology educators to take advantage of this development. We present some ideas for the use of thermal imaging for enhancing students' learning in biology using animals, humans and plants as subjects. The target student age group is middle school to high school level. Some fieldwork was involved in the studies while others can be carried out in a laboratory or classroom setting. There are unique advantages that render an infrared thermal imaging camera suitable and convenient for the studies in this article – it is compact in size and portable, which makes it ideal for fieldwork as well as allows for non-contact measurements which enable data acquisition from a distance from physically inaccessible subjects. We also provide a discussion on the strengths and limitations of using infrared thermal imaging in biology education.